Estudo do cotidiano de pequenos produtores rurais no ambiente da feira livre constituída a partir da gestão cooperativa - Gouvêa, Josiane Barbosa (2014)
From concepts designed by Certeau (2000), Heller (2000) and Lefebvre (1991), in this study I sought to understand how it is occurred the daily micro-practices in the fair managed by COPERAFA - Agribusiness Family Cooperative of the West of Paraná, in the city of Nova Aurora, despite the formalized management structure established by the cooperative to all units. The daily life as present Certeau (2000), Heller (2000) and Lefebvre (1991), is experienced by individuals whether they want to or not. Therefore, it is possible to notice that the everyday involves everyone equally. For Heller (2000) and Lefebvre (1991), however, that address the topic from a Marxist perspective, is the daily space of alienation, in which subjects simply reproduce formally established. Heller (2000), however, presents possibilities - moments - in which these individuals can break through the divestiture process. For Certeau (2000), in turn, the daily is source of inventiveness, in which subjects through practices micro resistors afford to build it. I then went to try to understand how such actions occur in an open market environment, managed through the concept of cooperatives. The concept of cooperation, which began in the mid-nineteenth century, through which individuals united in the pursuit of common goals, was lost in the course of time. From such considerations could see that the cooperative action in the current market, there are few who still seek support at some point the social foundations that originated them. Given this context is that I decided to enter myself in this research. This research is qualitative in nature. Data were collected through participant observation, semi structured interviews and oral history. The analysis was done by means of discourse analysis (DA) of the French line, from which seeks to analyze what is said beyond language. Realized in the process that even in cooperative environment, which was the object of this study, the capitalist discourse is hegemonic and determines the placement of individuals. Thus, the collective perspective is relegated to the background, to the detriment of individual growth. Checked in this way, we investigated the fair since its conception, power struggles and search for individual growth led the actions of those involved, culminating in the dismembering of units that originally formed the cooperative.